Protein Kinase Activity in Hepatitis B Virus - Albin, Catherine (1980)
Protein kinase activity was found in hepatitis B virions (Dane particles) purified from the plasma of hepatitis B virus-infected patients, in virion cores, and in hepatitis B core antigen particles purified from hepatitis B virus-infected hepatic tissue and was not found in purified hepatitis B surface antigen particle preparations free of Dane particles. Only a fraction of the major polypeptide (apparent size, 19,700 daltons) in Dane particle cores and hepatitis B core antigen particles from infected liver appeared to be phosphorylated, and phosphorylation changed the electrophoretic mobility in sodium dodecyl sulfate-polyacrylamide gels to that expected for a polypeptide of 20,600 daltons. Five minor polypeptides with apparent sizes between 38,000 and 63,000 daltons were phosphorylated in Dane particles and Dane particle core preparations but were not detected in hepatitis B core antigen particles from infected liver. None of these had electrophoretic mobilities corresponding to those of known hepatitis B surface antigen polypeptides. Prolonged storage of purified hepatitis B core antigen particles or incubation with human immunoglobulin G preparations containing antibody to the hepatitis B core antigen with or without antibody to the hepatitis B e antigen resulted in the conversion of the polypeptide with an apparent size of 20,600 daltons to ones with apparent sizes of 14,700 and approximately 6,000 daltons, suggesting proteolytic cleavage of the 20,600-dalton polypeptide under these conditions.